An Application design thinking in the internal quality audit system - Diah Aryani; Habibullah Akbar; Syahrizal Dwi Putra; Muhamad Bahrul Ulum (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Referring to Permenristekdikti No 62 of 2016, that every university must have an Internal Quality Assurance Standard (SPMI) policy and the implementation of an autonomous (independent) Internal Quality Assurance System. The quality of education with the process of building the culture required by higher education institutions, either through consistent implementation of the document, requires a standard on the guidelines for managing SPMI documents. This study aims to design a Higher Education Internal Quality Audit system using the Design Thinking method in computer science at Esa Unggul University. So that the results of this study can make a concrete contribution to information technology to assist the implementation of SPMI Internal Quality Audits which are carried out regularly. systemically and sustainably through PPEPP Standards of Higher Education.